2010
DOI: 10.1111/j.1365-294x.2010.04801.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of ninespine sticklebacks (Pungitius pungitius) in North America: glacial refugia and the origins of adaptive traits

Abstract: The current geographical distribution of the ninespine stickleback (Pungitius pungitius) was shaped in large part by the glaciation events of the Pleistocene epoch (2.6 Mya-1 Kya). Previous efforts to elucidate the phylogeographical history of the ninespine stickleback in North America have focused on a limited set of morphological traits, some of which are likely subject to widespread convergent evolution, thereby potentially obscuring relationships among populations. In this study, we used genetic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 80 publications
4
83
0
Order By: Relevance
“…Furthermore, as in the case of the three-spined stickleback, pelvic reduction in a Canadian nine-spined stickleback population appears to be controlled by a Pitx1 enhancer (Shapiro et al, 2006). However, this seems not be to be case in all nine-spined stickleback populations: Stringham et al (2000) have suggested that two other loci, unlinked to Pixt1, control pelvic reduction in two other populations of nine-spined sticklebacks (see also: Aldenhoven et al 2010;Shapiro et al 2009). Likewise, a recent QTL-analysis of genetic basis of pelvic reduction in a Fennoscandian nine-spined stickleback population has localized a large effect genetic factor responsible to pelvic reduction residing in a linkage group not containing Pitx1 (Shikano et al, unpublished data).…”
Section: Convergent Genetic Basis Of Parallel Phenotypic Evolution Inmentioning
confidence: 99%
“…Furthermore, as in the case of the three-spined stickleback, pelvic reduction in a Canadian nine-spined stickleback population appears to be controlled by a Pitx1 enhancer (Shapiro et al, 2006). However, this seems not be to be case in all nine-spined stickleback populations: Stringham et al (2000) have suggested that two other loci, unlinked to Pixt1, control pelvic reduction in two other populations of nine-spined sticklebacks (see also: Aldenhoven et al 2010;Shapiro et al 2009). Likewise, a recent QTL-analysis of genetic basis of pelvic reduction in a Fennoscandian nine-spined stickleback population has localized a large effect genetic factor responsible to pelvic reduction residing in a linkage group not containing Pitx1 (Shikano et al, unpublished data).…”
Section: Convergent Genetic Basis Of Parallel Phenotypic Evolution Inmentioning
confidence: 99%
“…Freshwater species have also performed south- and northward expansion through the repeated cycles of glaciation (Bernatchez and Wilson 1998; Caldera and Bolnick 2008; Aldenhoven et al. 2010), and the pattern and rate of dispersal have likely been influenced by landscape structures and spatial isolation among natural river drainages (Bilton et al. 2001; Craw et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important model species in evolutionary biology, genetics and behavioural research ( € Ostlund-Nilsson et al 2007;Meril€ a 2013). Pungitius pungitius has been the focus of many population genetic and phylogeographic studies using mitochondrial gene fragments (e.g., Aldenhoven et al 2010;Shikano et al 2010;Bae & Suk 2015;Wang et al 2015), but until now, only a partial assembly of the whole mitochondrial genome has been available from one individual originating from Hokkaido, Japan (Kawahara et al 2009). …”
mentioning
confidence: 99%